Morbimortalidade de idosos hospitalizados por fratura de fêmur – estudo de coorte - Keller, Gabriele Ruiz (2020)
Introduction: Currently, out of ten people, one is 60 years old or older, and projections point to a tendency for these numbers to increase. These individuals are more prone to some risks, including falls, with the possibility of serious complications such as femoral fractures, related to a high prevalence and association with death and disability. Objectives: To analyze morbidity and mortality during hospitalization and 3 years after discharge of elderly hospitalized for femur fracture in a hospital in central Rio Grande do Sul. Methods: This is a quantitative approach study with exploratory descriptive character. and prospective longitudinal design, characterized as a prospective cohort study. The study included elderly people hospitalized for femur fracture at the University Hospital of Santa Maria, and collected sociodemographic data (age, sex and living with whom), clinical-functional profile with the Senior Risk Index (ISAR), comorbidities index. Charlson (ICC), calf circumference (CP), Edmonton Fragility Scale (EFE) and Geriatric Depression Scale-4 (GDS 4) of outcomes from medical record analysis. This was performed during hospitalization and up to three years after hospital discharge. Results: From May 2015 to September 2016, 493 elderly were hospitalized, of these 11.2% (n = 55) entered the emergency room for femur fracture, mostly elderly aged 80 to 89 years (40% ) and female (69.1%). Of the elderly with femur fracture 74.5% (n = 41) had some degree of frailty, 13.0% (n = 7) had indicators of depression, 68.6% (n = 35) were classified as high risk of adverse event during hospitalization, 41.8% (n = 23) had a 79% chance of survival in one year and 53.1% (n = 128) had a CP <31 cm. It was observed that 75.9% (n = 41) of the elderly with fracture had hospital complications and 16.4% (n = 9) died during hospitalization. From hospital discharge up to 30 days we observed that 8.1% (n = 3) were readmitted, 87.5% (n = 35) had immobility after discharge, 24.4% (n = 10) had to visit the Emergency Room. after discharge and 7.0% (n = 3) died. The sociodemographic variables associated with femur fracture were age (p = 0.001) and gender (p = 0.001). Clinical and functional variables associated with femoral fracture admission were CHF (p = 0.018), risk of adverse event by ISAR (p = 0.010) and PC (p = 0.005). Femoral fracture is associated with intrahospital complications (p = 0.003), intrahospital immobility (p = 0.001), and was not associated with readmission outcomes (p = 0.541), intrahospital death (= 0.401) and death after 30 days (p = 0740). ). After 3 years, we observed that 45.3% (n = 27) of the elderly who survived after 30 days of hospitalization died, and 89% of the elderly who survived presented some degree of dependence for the activities, obtained from the Barthel These data suggest that femur fracture in the elderly causes physical changes since hospitalization, such as increased hospital complications and immobility, as well as after hospital discharge, where there was a high presence of death and functional dependence at 3 years after hospitalization.